Antigen-Specific vs. Neutralizing Antibodies Against Conditioned Media of Patients With Clostridioides difficile Infection: A Prospective Exploratory Study - Roth, Sophie; Jung, Philipp; Boone, James; Mellmann, Alexander; Nimmesgern, Anna; Becker, Sören L.; Berger, Fabian K.; von Müller, Lutz (Frontiers in Microbiology, 2022)
The immunological response against Clostridioides difficile (C. difficile) is crucial for an improved understanding of disease mechanisms and the development of novel therapeutic strategies. From April 2014 to February 2015, adult patients with C. difficile infection (CDI) were recruited, and the clinical course and treatment response were carefully monitored. On day 1, 3, and 6 after diagnosis, patient plasma samples were screened for anti-GDH (glutamate dehydrogenase), anti-TcdA, anti-TcdB, and anti-CWP84 (cell-wall protein 84) antibodies by ELISA. Additionally, neutralization assays of toxins from conditioned media of clinical isolates (RT010, RT014, and RT027) were performed. Most patients with CDI (n = 46) had antibodies against GDH (85%) and CWP84 (61%), but only few had antibodies against TcdA (11%) and TcdB (28%). We found patients with neutralizing antibodies against C. difficile toxins (conditioned media) produced by RT027 (26%). A subgroup of these samples could neutralize both toxins from RT027 and RT014 [11%, (5/46)]; however, no single sample neutralized only RT014. Overall, neutralizing antibody titers were low (≤1:16). In a one week follow-up of acute infection, we never observed an early booster effect with seroconversion or antibody increases, irrespective of disease severity. No correlation was found between the presence of antigen-specific (ELISA) or neutralizing antibodies and the clinical course of disease. Anti-TcdB but not anti-TcdA antibodies correlated with the occurrence of neutralizing antibodies. In conclusion, natural antibody titers against C. difficile toxins were absent or low and were not associated with disease severity. The correlation between the anti-TcdB with toxin neutralization confirms the importance of TcdB for virulence of CDI. Alternative sensitization strategies, e.g., through vaccine development, are required to overcome the regular low-titer antibody production following natural intestinal C. difficile exposure.